Preliminary - Gómez Botero, Maryory Astrid (Revista Facultad de Ingeniería Universidad de Antioquia, 2015)
Since the beginning of science, motivation for the search of knowledge was simple curiosity. However, nowadays the relationship between science and society has changed. Currently, conducting high quality research in some areas requires expensive equipment and very qualified staff, forcing researchers to compete fiercely for the limited resources and for a greater recognition. The pressure to publish research papers, and the lack of resources, has led to the detrimental of quality and ethics concerns of the published works, sometimes falling into scientific misconducts such as: scientific fraud (misrepresentation in data and results or manipulation thereof, plagiarism), unethical (fictitious authorship, repeated publications) and negligence in publishing (bibliographic mistakes).